2006
DOI: 10.1038/sj.ejhg.5201565
|View full text |Cite
|
Sign up to set email alerts
|

Identification of probable genotyping errors by consideration of haplotypes

Abstract: Undetected genotyping errors pose a problem in genetic epidemiological studies, as they may invalidate statistical analysis or reduce its power. Haplotype analysis requires an improved standard of the data, because a haplotype can be inferred correctly only if the genotypes of all its markers are correct. Here, we present a method that identifies probable genotyping errors in trio samples with the help of the estimated haplotype frequency distribution of the sample. If the likelihood of the most likely haploty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…Hardy-Weinberg equilibrium was checked on parental genotypes by w 2 -tests as implemented in Pedstats. 51 We checked for likely genotyping errors (e.g., manifesting as close double recombinants) using FAM-HAP 52 and set unlikely genotypes on missing for the respective individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Hardy-Weinberg equilibrium was checked on parental genotypes by w 2 -tests as implemented in Pedstats. 51 We checked for likely genotyping errors (e.g., manifesting as close double recombinants) using FAM-HAP 52 and set unlikely genotypes on missing for the respective individuals.…”
Section: Discussionmentioning
confidence: 99%
“…However, almost all existing algorithms estimate haplotype frequencies under the assumption that all of the genotype data are correct. In fact, large genotype data sets often have errors, though some genotyping errors can be partly detected using Mendel's laws as a check using trio design for pedigree data [33,34] . Furthermore, several studies have shown that even a small quantity of genotyping errors can have enormous impact on haplotype frequency estimates [1,24] , and then markedly affect haplotype-based linkage and association studies [31,32] .…”
Section: Discussionmentioning
confidence: 99%
“…Although some genotyping errors can be detected using Mendel's laws as a check for pedigree data, Gordon and coworkers [33] showed that the error-detection rate that has been estimated using trio designs does not exceed 30% for one diallelic marker. As Becker and coworkers [34] pointed out, the effect of undetected genotype errors may be exaggerated when haplotypes instead of single-marker loci are analyzed. Furthermore, they presented a method that detect genotyping errors in trios through using the estimated haplotype frequency distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, these methods have very limited power to detect errors in genotype data from small pedigrees such as mother-father-child trios, and do not apply at all to genotype data from unrelated individuals. (Becker et al, 2006) have recently introduced the use of population level haplotype frequency information for genotype error detection in trio data via a simple likelihood ratio test. However, detection accuracy of their method is severely limited by the reliance on explicit enumeration of most frequent haplotypes within short blocks of consecutive SNP loci.…”
Section: Kennedy Et Almentioning
confidence: 99%